High-Rate Stress Upturn of Ductile and Brittle Materials - Partom, Yehuda (European Journal of Applied Sciences, 2022)
Since the 1980s some researchers performed tests on ductile materials (mainly metals) at different strain rates, and saw a substantial increase of stress beyond strain rates of about 103-104/s. They termed this phenomenon high-rate stress upturn. Some 20 years later, other researchers observed a similar behavior in brittle materials (mainly concrete), but here the upturn started at a much lower rate of 1-10/s. Other researchers assumed that stress upturn is the same as flowstress upturn, according to the common approach to viscoplasticity since the 1960s. As a result, they didn’t believe that stress upturn may exist, and performed tests to show that doesn’t. This led to what has been known as the stress upturn controversy. Here we first describe high-rate stress upturn in ductile materials and in brittle materials, and then discuss the stress upturn controversy. We claim that viscoplasticity should be treated with our overstress approach and not with the widely used flowstress approach. When stress upturn is treated in this way, there is no reason to disclaim or deny the existence of stress upturn, and there’s no room for a stress upturn controversy.